The legend awakens - Dahlgren, Helena, 1980- (Dahlgren, Helena, 1980- Ödesyttarna., 2020)
"Join the Soul Riders as their adventures continue on the magical island of Jorvik...According to ancient myths, when the Soul Riders and their horses are gathered together, they will be able to defeat the evil that threatens the island. But Lisa and her friends don't quite understand this yet. And now that Lisa's horse, Starshine, has been stolen from Jorvik Stables, and her father has disappeared, there's no time to think about old stories. Together with Alex and Linda, Lisa embarks on a dangerous journey into Jorvik's magical landscape to save Starshine, and to find the answers they are searching for. At the same time, Anne is on her own mission. She must find her horse, Concorde, who seems to have been transported to the strange and dangerous world of Pandoria. But someone keeps whispering dark lies into Anne's head that make her doubt if there's any hope at all for the four girls"--from Back cover.